2016
DOI: 10.1038/cdd.2016.38
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin-2 modulates radiation-induced intestinal crypt progenitor/stem cell injury

Abstract: Intestinal crypt progenitor/stem (ICPS) cell apoptosis and vascular endothelial cell apoptosis are responsible for the initiation and development of ionizing radiation (IR)-evoked gastrointestinal syndrome. The signaling mechanisms underlying IR-induced ICPS cell apoptosis remain largely unclear. Our findings provide evidence that β-arrestin-2 (βarr2)-mediated ICPS cell apoptosis is crucial for IR-stimulated intestinal injury. βArr2-deficient mice exhibited decreased ICPS cell and intestinal Lgr5+ (leucine-ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…3C). The previous studies have shown that the number of surviving crypts following radiation was positively correlated with the number of ISCs (7,20). Therefore, we quantitatively analyzed ISC variation in response to radiation using Lgr5-GFP mice.…”
Section: Barr1 Is Involved In Radiation-induced Gi Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…3C). The previous studies have shown that the number of surviving crypts following radiation was positively correlated with the number of ISCs (7,20). Therefore, we quantitatively analyzed ISC variation in response to radiation using Lgr5-GFP mice.…”
Section: Barr1 Is Involved In Radiation-induced Gi Syndromementioning
confidence: 99%
“…Inhibition of ER stress may compromise the beneficial effects of barr1 deficiency on crypt regeneration in response to radiation IR has been shown to activate ER stress in IECs (20,21). To explore the role of ER stress in the barr1 deficiency-mediated increase in crypt regeneration after radiation, we applied the chemical agent salubrinal, a known ER stress inhibitor.…”
Section: Barr1 Is Involved In Radiation-induced Gi Syndromementioning
confidence: 99%
“…ARRB1 promotes stemness in non-small cell lung cancers, where it acts downstream of nicotinic acetylcholine receptors (18), as well as in leukemia-initiating cells where it promotes self-renewal (19). Furthermore, although ARRB1 inhibits apoptosis in intestinal stem cells induced by chemotherapy (20), ARRB2 may, under certain circumstances (e.g., ionizing radiation), promote apoptosis of intestinal crypt progenitor/stem cells (21). The role of ARRBs in bladder cancer has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the expression and clinicopathological significance of β-arrestin2 in CRC have not been reported. Liu et al (17) demonstrated that β-arrestin2 deficiency protracts the activation of the NF-κB pathway and suppresses radiation-induced intestinal crypt progenitor cell apoptosis (17). However, the role of β-arrestin2 β-arrestin2 promotes 5-FU-induced apoptosis via the NF-κB pathway in colorectal cancer in chemo-induced colon epithelial cell apoptosis remains to be explored.…”
Section: Introductionmentioning
confidence: 99%